2014
DOI: 10.1159/000369543
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Clonal Aberrations by Cytogenetic Analysis after Different Culture Methods and by FISH in 129 Patients with Chronic Lymphocytic Leukemia

Abstract: There are only a few cytogenetic analysis (CA) studies that directly compare the novel cultivation technique using immunostimulatory CpG-oligonucleotide DSP30/interleukin-2 (DSP30/IL2) with other culture methods. Therefore, parallel cultures of peripheral blood of 129 chronic lymphocytic leukemia (CLL) patients were set up in unstimulated cultures, in the presence of pokeweed medium (PWM), and with DSP30/IL2. Furthermore, CA results were compared with data obtained by FISH. Clonal aberrations were observed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…One of these effective immunostimulatory agents is DSP30. Recent studies have shown the efficacy of DSP30 on CLL cells either alone or with another agent (IL-2) [17][18][19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these effective immunostimulatory agents is DSP30. Recent studies have shown the efficacy of DSP30 on CLL cells either alone or with another agent (IL-2) [17][18][19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Other chromosomal abnormalities we determined are shown in Table 1 and common abnormalities diagnosed in CLL causing bad prognosis such as t 11;14 (q13;q32) [25][26][27] , dup 12 (q13q22), t 14;19 (q32;q13.1) accompanying with +12 and add 14 (q32) [26][27][28] were also present in our study. [17][18][19][20] . We investigated 13q14.3 deletion with both conventional karyotyping and iFISH techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Jenderny et al 19 studied different variants of cultures in the group of 129 patients with CLL. They were observing the number of metaphases obtained in cell cultures conducted in parallel: both unstimulated and stimulated (with the addition of pokeweed extract (PWM) to the medium and DSP30+IL2).…”
Section: Discussionmentioning
confidence: 99%